Startups’ innovation programmes: A food industry versus university cases - Elisha A. Govender; Elma van der Lingen (The Southern African Journal of Entrepreneurship and Small Business Management, 2024)
Background: Collaborations with external partners such as startups have been shown to bring agile and consumer-centric advantages to businesses to allow for future-proofing benefits as well as improve the rankings of universities. This type of collaboration can occur through innovation programmes with businesses and universities.